Functional condition in the preparatory period macrocycles by qualified handballers - Тищенко [Valeria Tishchenko] Валерія Олексіївна (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> 1024x768 <![endif]–> <!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: UK; mso-bidi-language: AR-SA;" lang="EN-US">Generalized data is modern scientific literature about physical development, the functional state of qualified handballers. The research of sportsmen’s HC "ZTR" at the beginning of the preparatory period game seasons 2012/2013. Is shown parameters ECG, central hemodynamics, cardiac rhythm variability and physical operability. The purpose of our research was to assist the coaching staff and handballers HC "ZTR" on the correct training program to achieve higher athletic performance <!–[if gte mso 9]> 1024x768 <![endif]–> <!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>